CHARACTERISTIC OF THE CARDIOLOGICAL CARE ORGANIZATION TO THE POPULATION OF KIEV REGION BY MATERIALS OF PATIENTS SURVEY - Ivanyuk, Anatoliy; Kanyura, Alexander (The Ukrainian Scientific Medical Youth Journal, 2020)
The aim: to study the state, problems and possible ways of improving the organization of cardiological care for rural residents based on the materials of a sociological survey of patients of district cardiology services in the Kiev region. Material and methods Using a specially developed questionnaire, a sociological survey of 829 patients, who applied to district cardiology services in the Kiev region was conducted in 2020. Results The analysis of the results of the survey showed that, in the opinion of the respondents, in order to improve the organization of cardiological care, it is nesessary to: optimize the organization of patient admission (51.4 ± 1.7%), increase the number of visits to cardiologists (67.5 ± 1.6%), improve the equipment of healthcare institutions (52.3 ± 1.7%), ensure the possibility of carrying out all laboratory tests prescribed by a doctor (45.9 ± 1.7%), expand the types of diagnostic examinations (45.8 ± 1.7%) , improve the qualifications of medical personnel (49.8 ± 1.7%) and introduce public-private partnership mechanisms in health care institutions while retaining them in state ownership (79.3 ± 2.2%). At the state level, according to the respondents, it is necessary to introduce National health insurance. Conclusions The results of the sociological study showed that the organization of cardiac care for the rural population of the Kiev region does not fully satisfy the population and requires optimization.